The Breast Implant May Delay Primary Coronary Intervention Case Report - Mohammed, MD, MRCPUK, MSc , Wael Abdulelah (International Journal of Innovative Research in Medical Science, 2022)
An Electrocardiography test is a reflection of the heart’s electrical activity, always being used in the emergency department to figure out the cause of chest pain. In terms of improving the quality and patient safety, investigators from Europe highlighted that breast implants are associated with abnormal ECG recordings, and suggested having an ECG before a breast implant procedure, which can be kept on an individual file and used for future comparison if needed. (Sok Sithikun Bun, et al 2017).